Global climate and energy policy after the COVID-19 pandemic : the tug-of-war between markets and politics (2020)
Before the COVID-19 pandemic of 2020, international climate diplomacy had settled into a regular yet disturbing routine. Every year, governments gathered to negotiate their climate commitments. Progress was haphazard and frustratingly slow, while economic growth and rising living standards contributed to the relentless growth of greenhouse gas emissions. The pandemic changed everything. For the first time since the end of the Cold War, global greenhouse gas emissions decreased rapidly. In April 2020, they had fallen by 17% from their 2019 levels, with almost half of the reduction from transportation. Researchers estimate that this reduction would translate into a 4%– 7% decrease for the entire year, depending on how quickly the world economy rebounds.